An Overview of the Current State of Social Ecological Economics Field: A Literature Review - Rivera-González, Gibrán; Cadena-López, Ayde; Escamilla-García, Pablo Emilio; Rivera , Angel Eustorgio (Journal of Ecohumanism, 2024)
In 2023, the World Economic Forum reported the existence of high-severity global risks in both the short and long term, including climate change, natural disasters and biodiversity loss. In response, Clive L. Spash, a scholar specializing in ecosocial issues, has proposed a paradigm shift that considers the interconnection between ecological, economic, and social challenges, advocating for approaches that go beyond the positivistic approach of orthodox economics. He refers to this approach as Social Ecological Economics (SEE), a school of thought that has received limited attention, evident from the scarcity of publications on the subject. In light of this, the objective of this paper is to provide an overview of the key elements that define Social Ecological Economics as an alternative field within ecological thought. To achieve this, a literature review was conducted, employing open and in vivo coding using Atlas.ti 9 software. The findings identify the core components of Social Ecological Economics, organized into categories such as background, characteristics, dimensions, problems, criticisms, foundations, and proposals. These categories highlight the distinctive identity of this school. As this study is exploratory in nature, a future research agenda is proposed to further examine the relevance of this approach in tackling pressing global issues.